vitro Production of Solasodine Alkaloid in Solanum nigrum under Salinity Stress - Ragab Abdel Gawwad1,2, Jasmin Å utkoviÄ‡1, Daria Ler1, Mohamed (Journal of Phytology, 2011)
The effect of Salinity stress on solasodine production by Solanum nigrum under tissue culture conditions has been investigated. Solasodine is steroidal alkaloid, alternative to diosgenin, which is used as a precursor for the commercial production of steroidal drugs. Salinity stress has been applied by adding NaCl to the culture medium MS, five concentrations were applied: 0.0 (control), 50, 100, 150, and 200 mM for 8 weeks. The obtained results show the possibility to increase solsasodine level production under salainity stress. However, the highest salinity stress concentration (200 mM of NaCl) has not significant when it is compared to (150 mM of NaCl) concentration. Positive correlations were observed between the NaCl levels and solasodine content accumulation, proline content and solasodine accumulation in Solanum nigrum calli. The solasodine production increased significantly as a result of increasing of NaCl concentrations. However, non-significantly differences were observed between 150 mM and 200 mM of NaCl on solasodine accumulation. Key words: Salinity, Solasodine, Solanum nigrum, Murashige and Skoog (MS) medium <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: "Book Antiqua","serif"; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Jasmin ŠutkoviÃ„â€¡ et al. In vitro Production of Solasodine Alkaloid in Solanum nigrum under Salinity Stress. J Phytol 3/1 (2011) 43-49